Performance and Analysis of the Spiral Representation Spatial Feature in Color-Spatial Image Retrieval System - Wang, Hui Hui; Narayanan, Kulathu Ramaiyer; Wang, Yin Chai; Abdelhamid, Abdesselam (IEEE, 2003)
The representation of spatial features is important for color-spatial based image retrieval systems for producing results that conform to human perception. The paper discusses the performance of the spiral representation of the spatial feature as proposed by Wang Hui Hui et al. (First Regional Malaysia-France Workshop on Image Processing in Vision Systems and Multimedia Commun., 2003). This novel approach addresses the issues of rotation and scaling invariance overcoming limitations of existing works.